The Model of the Gymnasium of Innovation in the Suburbs - Michilli, Mirta; Molina, Alfonso (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Starting from the experience gained in the suburbs of Bari, Milan, Palermo and Reggio Calabria, the OpenSPACE partnership worked on the drafting of a policy document to address new effective interventions against educational poverty. The project saw the engagement of a large community of practices and the activation of four Innovation Gyms. With a broad vertical partnership, also involving universities, the model is now spreading to the suburbs of Roma Capitale with the Smart & Heart Rome programme. The vision, strategies, model and tools are briefly described and references are provided for further investigation.